Desenvolvimento de dispositivos analíticos em plataformas de papel para análises volumétricas - Nogueira, Sandro Alves (2020)
This thesis demonstrates the development of acid-base, redox, complexometric and precipitation titrations on paper-based analytical devices (PADs) with and without the instruments such as smartphones for applications in chemical, biological, forensic, and quality control areas. The titrations in PADs present a performance similar to the classic methods using less reagents and generating less residues in a simpler platform and easier to prepared platform. The layout of the PADs was designed using a graphic software and subsequently printed on paper substrate through wax printing method. Prior to use, PADs were heated to melt the wax and create hydrophobic barriers. The acid-base titration in PAD was performed using a natural indicator prepared based on jabuticaba bark extract. Successive aliquots of titrant were added inside circular zones and the digital image was captured between each addition. The concentrations of acetic acid were determined in vinegar samples and the achieved values presented a difference between 5 and 8% when compared to conventional volumetric method. Redox titration was realized in a PAD composed of three zones folded like an origami, which were use to add the required reagents. The device was sealed with an adhesive tape at the bottom layer and successive aliquots of titrant were added to the sampling zone. The alcohol concentration was determined visually without the need for applications or software to process the color intensity. A linear behavior was observed for the concentration range from 0 to 50% (R2 = 0.992 and LOD = 2.1%). The proposed method was used to determine the alcohol content in seized whiskey samples from different brands. A total of 73% of the tested samples were correctly classified as adulterated. Redox titration was also evaluated to determine sodium hypochlorite in bleach obtaining a difference lower than 2% in comparison with the conventional method. For complexometric titration, it is necessary to use a buffer solution (pH 10) prepared with the mixture of sodium tetraborate and sodium hydroxide using eriochrome black T as an indicator and EDTA to complex the sample cation. All reagents were added in the PAD and allowed to dry prior to use. The distance of the red color formed by the cation complexation reaction was proportional to the analyte concentration. A linear behavior was observed in the concentration range between 7 and 250 mg / L of CaCO3 (R2 = 0.985 and LOD 10.74 mg / L of CaCO3). The distance-based complexometric assay was applied to determine the water hardness and calcium concentration in powdered milk sample. Finally, precipitation titration was performed on PADs by adding silver nitrate with the aid of a dropper and potassium chromate by immersing the device. After drying, the sample was added to the application zone and the concentration of chloride ions in samples of artificial saliva and physiological saline solution was obtained by measuring the distance resulting of the generated white precipitate. In the absence of any displacement, the color intensity was analyzed by a cell phone application. The linear range observed for chloride ion varied from 0.10 to 1.00% (R2 = 0.990 and LOD = 0.2%) for distance-based measurements and from 0.02 to 0.20% (R2 = 0.944 and LOD = 0.036%) for the color intensity recorded by the App. The methods proposed in this thesis did not differ significantly from classical titrations at 95% confidence level. The preparation of paper devices for titrations is simple, fast, and inexpensive. In addition, they are portable and do not require sophisticated instruments. Thus, the paper-based titrations open new perspectives for teaching analytical chemistry at all levels.